Kualitas Jasa Audit dalam Perspektif Dimensi Budaya Hofstede - Samirah Dunakhir (Business Management Journal, 2022)
This study aims to understand the role of cultural values on the perception of the importance of service quality factors in providing audit services. Hofstede presents six national cultural values, four of which have been used extensively in the accounting and auditing research literature. In Hofstede's cultural perspective, Indonesia is a country with cultural values: high power distance; low uncertainty avoidance; collectivism; and feminists. The sample in this study is the practitioners in audit market. Data was collected by using semi-structured interview technique. Data analysis was carried out using qualitative descriptive analysis with a Content Analysis approach. The themes in the interview transcripts were highlighted using Nvivo's QSR software program. The results showed that the cultural value of "expect good treatment" was identified in the respondents' answers during interviews that discussed the quality factor of audit services. This cultural value is one of the cultural values mentioned by Hofstede held by community groups with a cultural dimension of "high power distance". This shows that in discussing the rules that must be applied in maintaining audit quality, local cultural values must be considered. Different community groups have different cultural values.